Carboxyl Multiwalled Carbon‐Nanotube‐Stabilized Palladium Nanocatalysts toward Improved Methanol Oxidation Reaction. Issue 4 (23rd January 2015) - Wang, Yiran; He, Qingliang; Guo, Jiang; Wei, Huige; Ding, Keqiang; Lin, Hongfei; Bhana, Saheel; Huang, Xiaohua; Luo, Zhiping; Shen, T. D.; Wei, Suying; Guo, Zhanhu
Abstract Carboxyl‐functionalized multiwalled carbon nanotubes (MWNT‐COOH) decorated with palladium (Pd) nanoparticles (NPs, Pd–MWNT‐COOH) are prepared by using a one‐pot thermal decomposition method without addition of reductant or surfactant. An increased ratio of the D band to G band in Raman spectra and a decreased ratio of oxygen‐containing groups measured using X‐ray photoelectron spectroscopy suggest the interaction between Pd NPs and carboxyl groups in Pd–MWNT‐COOH. TEM studies reveal improved dispersion of Pd NPs after introducing MWNT‐COOH or MWNTs; the carboxyl groups act as anchors to perfectly disperse Pd NPs in Pd–MWNT‐COOH, which is responsible for the highest peak current of Pd–MWNT‐COOH for the methanol oxidation reaction. The best catalytic performance is observed in conditions that afford a balanced adsorption between hydroxide and methanol through varying the concentrations of methanol and KOH. Increasing temperature can also improve the catalyst performance due to enhanced reaction kinetics.